2021
DOI: 10.3390/catal11020255
|View full text |Cite
|
Sign up to set email alerts
|

Copper Phyllosilicates-Derived Catalysts in the Production of Alcohols from Hydrogenation of Carboxylates, Carboxylic Acids, Carbonates, Formyls, and CO2: A Review

Abstract: Copper phyllosilicates-derived catalysts (CuPS-cats) have been intensively explored in the past two decades due to their promising activity in carbonyls hydrogenation. However, CuPS-cats have not been completely reviewed. This paper focuses on the aspects concerning CuPS-cats from synthesis methods, effects of preparation conditions, and dopant to catalytic applications of CuPS-cats. The applications of CuPS-cats include the hydrogenation of carboxylates, carboxylic acids, carbonates, formyls, and CO2 to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 206 publications
(433 reference statements)
0
3
0
Order By: Relevance
“…Cu-based heterogeneous catalysts have been used in the chemical industry to hydrogenate unsaturated C–O bonds. The abundant and inexpensive nature of Cu has attracted much attention for novel catalyst designs for hydrogenation despite significant progress in developing precious metals with outstanding functions as promising catalysts. In this context, Cu-based catalysts with ZnO counterparts have been recognized as powerful materials for hydrogenating CO 2 to methanol for decades. Recently, tremendous efforts have been devoted to establishing Cu-based catalysts with novel metallo-counterparts for a range of CO 2 transformations. The wide-ranging availability has increased the indispensability of Cu-based catalysts for large-scale CO 2 capture and utilization, in conjunction with renewable energy directed toward net-zero CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Cu-based heterogeneous catalysts have been used in the chemical industry to hydrogenate unsaturated C–O bonds. The abundant and inexpensive nature of Cu has attracted much attention for novel catalyst designs for hydrogenation despite significant progress in developing precious metals with outstanding functions as promising catalysts. In this context, Cu-based catalysts with ZnO counterparts have been recognized as powerful materials for hydrogenating CO 2 to methanol for decades. Recently, tremendous efforts have been devoted to establishing Cu-based catalysts with novel metallo-counterparts for a range of CO 2 transformations. The wide-ranging availability has increased the indispensability of Cu-based catalysts for large-scale CO 2 capture and utilization, in conjunction with renewable energy directed toward net-zero CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Among the different non-noble metal-based catalytic systems, the hydrosilicate materials -natural minerals, which can be obtained synthetically, are actively used in heterogeneous catalysis. [28] Copper phyllosilicates (PhylS) with the chrysocolla-like structure Cu 2 Si 2 O 5 (OH) 2 • xH 2 O were shown to be the precursors of active catalysts for hydrogenation of esters [29,29,30] and alkynes, [31] as well as for the hydrogenolysis processes. [8,32,33] Recently, we have shown that the copper phyllosilicate based materials are active catalysts in a liquidphase hydrogenation of different nitro-arenes, [34] including even dinitro-and trinitrobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diversity of different copper catalytic systems, copper phyllosilicates occupy a special place due to their unique structure. Copper phyllosilicate, or chrysocolla, is a silica-supported copper material with a sandwich structure consisting of octahedra CuO 6 layers possessed between tetrahedra SiO 4 layers [ 6 ]. In contrast to traditional SiO 2 -supported copper oxide, phyllosilicate has an improved thermal stability, higher copper species dispersion, and larger specific surface area due to its layered structure [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%